Euphorbia hirta Leaf Ethanol Extract Suppresses TNF-α/IFN-γ-Induced Inflammatory Response via Down-Regulating JNK or STAT1/3 Pathways in Human Keratinocytes - Tae-Young Gil; Sung-Chul Kang; Bo-Ram Jin; Hyo-Jin An (Life, 2022)
Skin inflammation may cause allergic diseases such as allergic rhinitis, asthma, and atopic dermatitis. Euphorbia hirta (E. hirta) is a member of the Euphorbiaceae family and is well-known for its anti-asthma effects. E. hirta has traditionally been used to treat respiratory ailments, dysentery, jaundice, and digestive problems. However, its effects on skin inflammation remain unclear. Here, we determined the effects of 70% ethanol extract of E. hirta leaves (ELE) in vitro using human keratinocyte HaCaT cells, which constitute most epidermal skin cells. We determined the inhibitory effects of ELE on the inflammation caused by tumor necrosis factor (TNF)-α/interferon (IFN)-γ in keratinocytes using ELISA, immunoblotting, and qRT-PCR assay. ELE was found to reduce the production and mRNA expression of pro-inflammatory cytokines such as TNF-α or interleukin-6 and the expression of various proteins, including signal transducers, activators of transcription 1/3, and mitogen-activated protein kinase. Expression levels of these proteins were found to be upregulated in the TNF-α/IFN-γ-stimulated condition and downregulated by ELE treatment. These results indicate that ELE protects HaCaT cells against TNF-α/IFN-γ-induced skin inflammation.